Development of large‐scale Birkeland currents determined from the Active Magnetosphere and Planetary Electrodynamics Response Experiment. Issue 9 (7th May 2014) - Anderson, B. J.; Korth, H.; Waters, C. L.; Green, D. L.; Merkin, V. G.; Barnes, R. J.; Dyrud, L. P.
Abstract The Active Magnetosphere and Planetary Electrodynamics Response Experiment uses magnetic field data from the Iridium constellation to derive the global Birkeland current distribution every 10 min. We examine cases in which the interplanetary magnetic field (IMF) rotated from northward to southward resulting in onsets of the Birkeland currents. Dayside Region 1/2 currents, totaling 25% of the final current, appear within 20 min of the IMF southward turning and remain steady. Onset of nightside currents occurs 40 to 70 min after the dayside currents appear. Thereafter, the currents intensify at dawn, dusk, and on the dayside, yielding a fully formed Region 1/2 system 30 min after the nightside onset. The results imply that the dayside Birkeland currents are driven by magnetopause reconnection, and the remainder of the system forms as magnetospheric return flows start and progress sunward, ultimately closing the Dungey convection cycle.